Fentanyl Promotes Breast Cancer Cell Stemness and Epithelial-Mesenchymal Transition by Upregulating α1, 6-Fucosylation via Wnt/β-Catenin Signaling Pathway - Yang, Hong-Fang; Yu, Ming; Jin, Hui-Dan; Yao, Jia-Qi; Lu, Zhi-Li; Yabasin, Iddrisu B.; Yan, Qiu; Wen, Qing-Ping (Frontiers in Physiology, 2017)
ABSTRACT Cancer pain is a common and severe complication of human breast cancer, and relieving pain is fundamental strategy in the treatment. Fentanyl, as an opioid analgesic, is widely used in breast cancer patients. However, little is known about its effects on stemness and epithelial-mesenchymal transition (EMT) of breast cancer cells. Aberrant protein glycosylation is involved in cancer malignancy. The α1, 6-fucosylation is an important type of glycosylation, and the elevated α1, 6-fucosylation catalyzed by fucosyltransferase Ⅷ (FUT8) is found in many tumors. However, whether 1, 6-fucosylation is involved in regulating stemness and EMT, and stimulated by fentanyl is not clear. In this study, we found that fentanyl induced stemness and EMT in MCF-7 and MDA-MB-231 breast cancer cells by analysis of sphere formation, expression of stemness markers (Sox2, Oct4) and EMT markers (N-cadherin, E-cadherin and Vimentin). Results also showed that fentanyl upregulated FUT8 gene and protein expression by qPCR, Western blot and immunofluorescent staining, as well as α1, 6-fucosylation level by Lectin blot and Lectin fluorescent staining. Furthermore, decreased or blocked α1, 6-fucosylation by FUT8 siRNA transfection or LCA Lectin blockage reduced stemness and EMT. Additionally, fentanyl activated the key molecules and target genes in Wnt/β-catenin signaling pathway. LGK-974 (an inhibitor of Wnt ligands) suppressed fentanyl-mediated upregulation of α1, 6-fucosylation, stemness and EMT. The results of tumor xenograft demonstrated that fentanyl enhanced tumor growth, α1, 6-fucosylation, stemness and EMT. Taken together, our study reveals that fentanyl upregulated FUT8 expression, which increased α1, 6-fucosylation level through activation of Wnt/β-catenin signaling pathway, thereby, induce stemness and EMT of breast cancer cells. This study suggest a potential side effect of fentanyl in the treatment of cancer, which may guide the safety of fentanyl in the clinical application.